Development And Validation of a LC-MS Compatible Method for Quantification of Degradation Impurities of Clofazimine Using UHPLC - Surya Narayana Murty, Nagulakonda Naga Veera Venkata Sri; Bhattacharjee, Akash; Krishnamurthy, Tatikonda; Rao, Muguda R. P.; Rao, Gollapalli N. (Current Pharmaceutical Analysis, 2020)
Background: Clofazimine has antibacterial and leprostatic properties, which has its use in Multidrug Therapy (MDT) of leprosy. As per the FDA guidance for industry, each NDA and ANDA must include the analytical procedures necessary to ensure the identity, strength, quality, purity, and potency of the drug substance and drug product. However, it was noticed that no stability indicating method is available in the literature for the estimation of degradation impurities of Clofazimine. Objective: Objective of the proposed work is to develop and validate a rapid, specific, linear, robust, accurate and sensitive Ultra High-Performance Liquid Chromatography (UHPLC) method with LC-MS compatible mobile phase for the quantification of degradation impurities of Clofazimine in a pharmaceutical dosage form (topical gel 0.5% w/w). Method: Ultra High-Performance Liquid Chromatography equipped with PDA and Tunable UV (TUV) detector at a wavelength of 284 nm, stationary phase with a fused core particle technology, LC-MS compatible mobile phase was employed in this study. Gradient elution was employed for ensuring the selectivity of degradation impurities and clofazimine. This method was validated in accordance with ICH Q2 guidelines. This is the first reported Ultra High-Performance Liquid Chromatography method for estimation of degradation impurities of clofazimine. Results: The method showed good linearity over the range of 0.25 -1.5μg/ml of clofazimine. All the validation parameters were within the acceptance criteria. The product is found to degrade in the acid and peroxide degradation condition. The major degradant impurities are eluted at relative retention times of 0.35, 0.89 and 0.95. The developed method successfully separated the degradation products of clofazimine and able to quantitate accurately in its formulation. Conclusion: To date, there is no UHPLC method for determination of degradation impurities of clofazimine. in pharmaceutical dosage forms. Being a specific, linear, accurate and robust method, this would help in determining the chemical stability of drug product during the product development as well as in the shelf life of the drug product.
Keywords: chromatography